2021
DOI: 10.1021/acs.nanolett.1c02491
|View full text |Cite
|
Sign up to set email alerts
|

Forces, Kinetics, and Fusion Efficiency Altered by the Full-Length Synaptotagmin-1 -PI(4,5)P2 Interaction in Constrained Geometries

Abstract: A mechanism for full-length synaptotagmin-1 (syt-1) to interact with anionic bilayers and to promote fusion in the presence of SNAREs is proposed. Colloidal probe force spectroscopy in conjunction with tethered particle motion monitoring showed that in the absence of Ca2+ the binding of syt-1 to membranes depends on the presence and content of PI­(4,5)­P2. Addition of Ca2+ switches the interaction forces from weak to strong, eventually exceeding the cohesion of the C2A domain of syt-1 leading to partial unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…28 In agreement, Cafiso and collaborators 35 hypothesized that Syt1 could mediate the transition during a fusion event by either lowering an energy barrier toward pore expansion (the metastable fusion pore) or by preventing the system from getting trapped at an early intermediate state (a just nucleated fusion pore), as also proposed by Kiessling and collaborators. 85 Moreover, Chapman and collaborators 86 recently observed that the interaction of Syt1 with PIP 2 serves to stabilize opening of fusion pores, while Janshoff and collaborators 87 suggested that Syt1 collaborates to accelerate fusion kinetics in the presence of Ca 2+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…28 In agreement, Cafiso and collaborators 35 hypothesized that Syt1 could mediate the transition during a fusion event by either lowering an energy barrier toward pore expansion (the metastable fusion pore) or by preventing the system from getting trapped at an early intermediate state (a just nucleated fusion pore), as also proposed by Kiessling and collaborators. 85 Moreover, Chapman and collaborators 86 recently observed that the interaction of Syt1 with PIP 2 serves to stabilize opening of fusion pores, while Janshoff and collaborators 87 suggested that Syt1 collaborates to accelerate fusion kinetics in the presence of Ca 2+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ca 2+ -bound synaptotagmin-1 is inserted to native vesicle membranes such as synaptic vesicles and large dense-core vesicles (LDCVs) that contain anionic phospholipids 10 . However, ATP electrostatically prevents the cis- interaction of synaptotagmin-1, whereas the trans -interaction of synaptotagmin-1 to the plasma membrane remains active to mediate Ca 2+ -dependent vesicle fusion, because PIP 2 overcomes the inhibitory effect of ATP by increasing the membrane-binding affinity of the C2AB domain 10, 11, 12 .…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that despite the receptor heterogeneity of cell-surface glycans, HAfps can still productively engage with a target membrane across a large range of distances and that the efficacy of IAV fusion is enhanced by receptor flexibility. This work has implications for how the rigidity and distance between biological interfaces impact other membrane fusion processes and downstream signaling. While our DNA tethering methodology yields several mechanistic insights into the role of viral receptor length and flexibility in IAV fusion, direct visualization of the membrane interface would further elucidate the role of tether mobility in the mechanism of IAV fusion.…”
Section: Discussionmentioning
confidence: 99%